2022
DOI: 10.32598/hdq.8.1.419.2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Social Capital on the Mental Health of the University Students During the COVID-19 Pandemic With the Mediation of the Resilience Variable

Abstract: Background: This research was conducted to evaluate the effect of social capital on the student’s mental health with the mediation of resilience during the COVID-19 pandemic. Materials and Methods: The research is based on the objective criterion in the applied research group and the data collection method criterion in the survey research group. The statistical population includes the students of the state universities of Tehran and Islamic Azad University Science and Research Branch. The sample size was estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Several empirical studies have supported the mediation role of psychological resilience between social capital and mental health (Adelinejad et al 2022;Gao et al 2018;Khaksar et al 2019). A study conducted by Gao et al (2018) in China revealed that persons with a greater degree of social capital, as measured among those living with HIV/AIDS, tend to have stronger psychological resilience, leading to improved mental health outcomes.…”
Section: The Mediation Role Of Psychological Resilience Between Socia...mentioning
confidence: 99%
See 4 more Smart Citations
“…Several empirical studies have supported the mediation role of psychological resilience between social capital and mental health (Adelinejad et al 2022;Gao et al 2018;Khaksar et al 2019). A study conducted by Gao et al (2018) in China revealed that persons with a greater degree of social capital, as measured among those living with HIV/AIDS, tend to have stronger psychological resilience, leading to improved mental health outcomes.…”
Section: The Mediation Role Of Psychological Resilience Between Socia...mentioning
confidence: 99%
“…A study conducted by Gao et al (2018) in China revealed that persons with a greater degree of social capital, as measured among those living with HIV/AIDS, tend to have stronger psychological resilience, leading to improved mental health outcomes. Similarly, Adelinejad et al (2022) revealed that social capital significantly influences university students' psychological resilience and mental health. Additionally, Khaksar et al (2019) demonstrated that social capital plays a vital role in diminishing job burnout among employees in stressful settings, with psychological resilience acting as a facilitating role.…”
Section: The Mediation Role Of Psychological Resilience Between Socia...mentioning
confidence: 99%
See 3 more Smart Citations